Three new species of Xyalidae (Nematoda: Monhysterida) from Argentinean coast - Russo, Virginia Lo; Pastor, Catalina T. (Zootaxa, 2026)
Three new species of free-living marine nematodes belonging to the family Xyalidae are described from the Argentinean coast: Rhynchonema paraseparatum sp. nov., Rhynchonema bicuspidatum sp. nov., and Prorhynchonema uncinoa sp. nov. Rhynchonema paraseparatum sp. nov. is characterized by an annulated cuticle without projections, L-shaped spicules, and a gubernaculum with dorsal projections. Rhynchonema bicuspidatum sp. nov. has an annulated cuticle with anterior and posterior projections, a uniquely shaped gubernaculum with two distal tips, and longitudinal bands along the mid-body. Prorhynchonema uncinoa sp. nov. is characterized by a gubernaculum with hook-like distal structures and amphids located well posterior to the buccal cavity. These findings expand the taxonomic knowledge and geographic distribution of Xyalidae in the Southern Hemisphere.